Pengaruh Efikasi Diri, Fasilitas Belajar, dan Kemandirian Belajar terhadap Hasil Belajar Siswa Minu Berbek Waru - M. Jamal Abdul Naser; Eli Masnawati; Didit Darmawan (Departement of Mathematics Education, 2024)
It is important to remember that learning outcomes are an important aspect in measuring student performance and the effectiveness of the learning process in an educational institution such as MINU Berbek Waru Sidoarjo. Measuring student performance is not only limited to academic grades, but also includes understanding concepts, applying skills, and developing critical thinking skills. This study is quantitative, with the main objective of measuring the extent of the influence of self-efficacy, learning facilities, and learning independence on the learning outcomes of MINU Berbek Waru students. The results of this study revealed that self-efficacy, learning facilities, and learning independence had a positive and significant influence on the improvement of learning outcomes of MINU Berbek Waru students. Keywords: Self-Efficacy, Learning Facilities, Learning Independence, Learning Outcomes